MicroRNA-17~92 inhibits colorectal cancer progression by targeting angiogenesis. Issue 2 (1st July 2016) - Ma, Huabin; Pan, Jin-Shui; Jin, Li-Xin; Wu, Jianfeng; Ren, Yan-Dan; Chen, Pengda; Xiao, Changchun; Han, Jiahuai
Highlights: MiR-17~92 suppresses tumor progression in a transgenic mouse model of colorectal cancer. MiR-17~92 inhibits tumor angiogenesis in CRC mouse model through suppressing expression of several angiogenesis-inducing genes. High expression of miR-17~92 correlates with reduced angiogenesis in male colorectal cancers in human patients. Abstract: The miR-17~92 microRNA (miRNA) cluster host gene is upregulated in a broad spectrum of human cancers including colorectal cancer (CRC). Previous studies have shown that miR-17~92 promotes tumorigenesis and cancer angiogenesis in some tumor models. However, its role in the initiation and progression of CRC remains unknown. In this study, we found that transgenic mice overexpressing miR-17~92 specifically in epithelial cells of the small and large intestines exhibited decreased tumor size and tumor angiogenesis in azoxymethane and dextran sulfate sodium salt (AOM-DSS)-induced CRC model as compared to their littermates control. Further study showed that miR-17~92 inhibited the progression of CRC via suppressing tumor angiogenesis through targeting multiple tumor angiogenesis-inducing genes, TGFBR2, HIF1α, and VEGFA in vivo and in vitro . Collectively, we demonstrated that miR-17~92 suppressed tumor progression by inhibiting tumor angiogenesis in a genetically engineered mouse model, indicating the presence of cellular context-dependent pro- and anti-cancer effects of miR-17~92.